Implementation of LQR controller on coupled tank liquid level system - Mohd Shahizan, Shapii (2008)
Coupled Tank system used for liquid level control is a model of plant that has usually been used in industries especially chemical process industries. Level control is also very important for mixing reactant process. The basic concept of how the coupled tanks system work in this project is by using computer as the main control where user can control the level of liquid in one tank or both tanks. To control the liquid level automatically, a controller is needed to be implemented. For this project, LQR controller is used. Advantech USB 4716 DAQ is a device use to communicate between computer and the computer. Basically, this project focuses on the design and modeling for coupled tanks system with the implementation of LQR controller. Mathematical model of the system is first taken from manual book provided by AISB Sdn. Bhd. and verified by MATLAB. Based on the simulation result, the value of state feedback produce by LQR is used in Visual Basic to see the response in real time process.